2012
DOI: 10.1161/circulationaha.112.110460
|View full text |Cite
|
Sign up to set email alerts
|

The Safety of Cardiopulmonary Exercise Testing in a Population With High-Risk Cardiovascular Diseases

Abstract: Background-Cardiopulmonary exercise testing (CPX) with measurement of peak oxygen uptake (VO 2 ) is a powerful test for assessment and quantification of functional impairment resulting from cardiovascular disease. The safety of CPX has been established in patients with coronary artery disease and congestive heart failure, but clinical use of CPX in other cardiac diseases has been limited, in part because of a paucity of safety data. This study investigates the safety of CPX in a heterogeneous cohort of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(60 citation statements)
references
References 40 publications
2
53
0
5
Order By: Relevance
“…Safety Adverse events are rare during properly supervised tests (table 1). In the largest study looking at 5060 cardiopulmonary exercise tests in high-risk cardiovascular patients, including 196 PAH patients, the adverse event rate was 0.16% with no fatalities [27]. In a study of PAH in adults, there were no events in 242 tests [28].…”
Section: Methodsmentioning
confidence: 99%
“…Safety Adverse events are rare during properly supervised tests (table 1). In the largest study looking at 5060 cardiopulmonary exercise tests in high-risk cardiovascular patients, including 196 PAH patients, the adverse event rate was 0.16% with no fatalities [27]. In a study of PAH in adults, there were no events in 242 tests [28].…”
Section: Methodsmentioning
confidence: 99%
“…However from these central variables, a number of other prognostically important markers of cardiorespiratory function can also be derived (Table 1). Maximal exercise testing with integrated gas exchange is a safe procedure, even in populations with higher underlying risk diagnoses; including heart failure, hypertrophic cardiomyopathy, pulmonary hypertension, aortic stenosis, and chronic obstructive pulmonary disease (Skalski, Allison, & Miller, 2012). Reported rates of death for patients during maximal exercise testing are approximately 2 to 5 per 100,000 clinical exercise tests (Balady et al, 2010).…”
Section: Data Capturementioning
confidence: 99%
“…Multiple studies in adults [83,96,97] and children [89,98,99] have suggested that this is not a problem. In the largest study looking at CPET in high risk cardiovascular patients (n = 5060 CPET events) [97], adverse event rate was 0.16% with no fatalities. In a study dedicated to PAH [96], there were no events in 242 tests.…”
Section: Cardiopulmonary Exercise Testingmentioning
confidence: 99%